Stereoselective Alkene Isomerization over One Position - Larsen, Casey R; Grotjahn, Douglas B (Journal of the American Chemical Society, 2012)
Although controlling both the position of the double bond and E:Z selectivity in alkene isomerization is difficult, 1 is a very efficient catalyst for selective mono-isomerization of a variety of multifunctional alkenes to afford >99.5% E-products. Many reactions are complete within 10 min at room temperature. Even sensitive enols and enamides susceptible to further reaction can be generated. Catalyst loadings in the 0.01–0.1 mol% range can be employed. E-to-Z isomerization of the product from diallyl ether was only <10–6 times as fast as its formation, showing the extremely high kinetic selectivity of 1.